CLUSTER-BASED PRIORITY LIST GENERATION FOR RESOURCE-CONSTRAINED PROJECT SCHEDULING PROBLEMS - Öztürk, Ahmet Melik; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Constructive Heuristics for the Resource Constraint Project Scheduling Problems (RCPSP) are preferred scheduling methods when the project network broadens. Then, to generate a good schedule from these heuristics, the priority list used in the algorithm becomes crucial. This paper proposes a Cluster-Based Priority List (CB-PL) method for generating lists to improve makespans of schedules obtained from constructive heuristics. The method creates more intellectual priority lists that generate lower makespans. The approach is built and fine-tuned upon the existing relative literature. The performance of the method is measured by comparing the makespan results. The experiment for the comparison uses serial and parallel scheduling schemes with seven priority rules. Then the experiment is tested through a set of benchmark data. Finally, schedules obtained through the CB-PL showed significant makespan reductions and increases in an overall number of better solutions.